Resolving taxonmic discrepancies: Role of Electronic Catalogues of Known Organisms - Chavan, Vishwas Shravan; Rane, Nilesh Sunil; Watve, Aparna; Ruggiero, Michael (Biodiversity Informatics, 2005)
There is a disparity in availability of nomenclature change literature to the taxonomists of the developing world and availability of taxonomic papers published by developing world scientists to their counterparts in developed part of the globe. This has resulted in several discrepancies in the naming of organisms. Development of electronic catalogues of names of known organisms would help in pointing out these issues. We have attempted to highlight a few of such discrepancies found while developing IndFauna, an electronic catalogue of known Indian fauna and comparing it with existing global and regional databases.